CHARACTERISTICS RELATED TO THE EXCHANGE OF OPINIONS OF THE TEACHER WHEN INTRODUCING PRIMARY CLASS STUDENTS TO COMMUNICATION - Khudoykulova, Fazilat (Журнал иностранных языков и лингвистики, 2022)
in this article, the interaction between the teacher and the student in the activities of the teacher, the peculiarity of influencing the mind of the student during the conversation and activities of the teachers, the main essence of the teacher’s communicative ability, the student’s it talks about the process of exchange of ideas and how to influence the logical thinking skills of the child on the basis of the pedagogue’s international research programs.